Isolation and molecular characterization of Acanthamoeba spp. from Iraqi patients with Keratitis (Baghdad Science Journal, 2024)
Isolation and molecular characterization of Acanthamoeba spp. related corneal infections in Iraqi Patients. A total of 96 samples from corneal scraps and contact lenses were gathered from corneal patients for the current trial, which runs from November 2020 to May 2021. All plates were checked, classifying them as positive or negative morphologically identification of Acanthamoeba spp. where PCR analysis, which entails the targeted amplification of nucleic acids, has been carried out, and where The 18s rRNA gene's DF3 region was the focus of the isolated strains' sequences. Three patients had Acanthamoeba spp. infections, according to the findings. then the sequence analysis was performed using the NCBI tool, which showed the presence of 2 different genotypes, two strains were grouped into the T3 genotype, one from T4, then they were registered in GeneBank under number accession (MZ427912, MZ349042) respectively. To our knowledge, these are the first reported cases of Acanthamoeba keratitis in Iraq.